أثر مقاصد الشریعة في التشریع الأسري ـ نماذج مختاره ـ - نسیب, هادیة (University of Eloued جامعة الوادي, 2017)
تناولت هذه الدراسة موضوع أثر مقاصد الشريعة في التشريع الأسريـ نماذج مختارهـ، حيث تعتبر مقاصد الشريعة مجالاً مهماً في التشريعات الأسرية والتي يظهر من خلالها أهم خصائص الشريعة الإسلامية، الرحمة والرفق والسهولة، حيث استُهلت الرسالة بدراسة تأصيلية لمقاصد الشريعة، ثم تطرقت إلى أقسام التشريع الأسري وبيان العلاقة بينه وبين مقاصد الشريعة. كما اُنصب اهتمام هذا البحث على بيان أثر المقاصد على الأسرة بنماذج تطبيقية مختاره، وقد عمدت إلى اختيار مسألة واحدة في كل مرحلة من مراحلها، بداية من أسس ومعايير اختيار شريك الحياة، ثم وجود الوليّ في عقد الزواج، إلى الحضانة في حال تعثر الحياة الزوجية. والغرض من كل هذا إبراز مقاصد الشريعة الإسلامية وإثبات أثرها في فقه الأسرة.This study dealt with the subject of the purposes of Islamic law of the family legislation – selected models- since the purposes of Islamic laws is considered as an important field in the family legislation which shows the main characteristics of the Islamic law (mercy, mildness, ease). This work started with a thorough study of the Islamic purposes law then, it touched the parts of the family legislation and explained the relationship between both these parts and the purposes of the Islamic law. Moreover, we gave importance in this research to the statement of purposes on the family with selected practical samples, we spotted light on only one problem and its steps starting with principles and standards of choosing a life partner, then we moved to a study of the presence of a legal guardian in the act of marriage. After that, we shifted to the custody in case of divorce. all this was done to show the purpose of Islamic law and proofing its main role in the jurisprudence of the family.
مذكرة ماستر تخصص اصول فقه
Keywords: الأسرة، مقاصد، أثر، زواج; Family, makassed, trace, marriage